Geology of Parliament Buildings 3. Building Stones of Ontario's Provincial Parliament Building - Freeman, E. (Geoscience Canada, 2003)
Summary Completed in 1893, Ontario's Parliament Buildings were designed to hold all the government and elected representatives' offices. Expansion of government services soon required the construction of several other buildings to house government offices. Using in its design mostly Canadian stone from Ontario and Quebec, the 1893 building was Toronto's first full Richardson Romanesque building. Partial reconstruction after a fire and the addition of a new wing combined to bring a variety of building stones to the site. A brief history of the building, and the properties of its stones - theirstrengths and weaknesses, is presented along with the result of a century of exposure to the city's weather, and the maintenance schedule underway to ensure another century of use.